From food waste to value‐added surplus products (VASP): Consumer acceptance of a novel food product category. Issue 1 (13th October 2017) - Bhatt, Siddharth; Lee, Jeonggyu; Deutsch, Jonathan; Ayaz, Hasan; Fulton, Benjamin; Suri, Rajneesh
Abstract: Over one third of the food we produce is never consumed. Such a high rate of food waste is appalling. To address this, researchers have focused on creating foods from surplus ingredients or ingredients obtained during the manufacturing of other foods. We term such foods as value‐added surplus products. But will consumers accept products made from ingredients destined for the trash bin? A series of studies that test 3 different cues that consumers utilize to evaluate foods suggests strong potential for consumer acceptance, and even preference for such foods. Study 1 tested description for value‐added surplus products alongside those for conventional and organic foods to understand whether consumers discriminate between these foods. Study 2 tested consumer preference for 9 product labels for value‐added surplus products. Study 3 examined whether benefits to self or to others will differentially influence consumers' perceptions of such value‐added foods. Collectively, these studies suggest a strong potential for such foods to command position as a new category of foods that is distinct from both conventional as well as organic foods.